The Impact of River Tourism on the Development of the Demarcated Regions in Specific (Post-pandemic Crisis) Contexts: The Case of Cruise Ships - Sousa, Bruno (2022)
Cruise tourism is a very attractive and growing segment in the European context. In particular, Portugal (i.e. the Douro region) is a tourist destination strongly aimed at consumers of nautical and coastal tourism. The pandemic of the new coronavirus (i.e. covid-19) caused strong changes in the management and marketing of tourist destinations, as well as in cruise tourism (e.g. trips were canceled, security rules were implemented). Covid-19 triggered an unprecedented global health and economic crisis with severe, and potentially structural, consequences for the cruise world. The growth (or decrease) of coastal-motivated tourist flows affects the local development of the regions and, consequently, the local community. This manuscript aims to understand the Impact of River Tourism on the Development of the Demarcated Region of Alto Douro Wine Region (in specific, the Case of Cruise Ships) in Portugal. The manuscript presents inputs for tourism marketing and for the management of coastal tourist destinations. At the end, lines of research for the future will be presented.